ANALISIS KONTRIBUSI DAN EFEKTIVITAS PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KOTA BANJARMASIN - Resti Sylvianur; Eny Fahraty (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
The purpose of this study is to (1) know the level of restaurant tax growth rate of the City of Banjarmasin (2) find out how much the contribution of restaurant tax to the original income of Banjarmasin City (3) in order to find out how far the restaurant tax effectiveness Banjarmasin City.The data taken by this study uses secondary data and primary data with annual time series data from 2013 to 2018. The data source is obtained from the Banjarmasin City Financial Board. This research uses quantitative descriptive methods.The results of this study is that the rate of tax growth in restaurants in Banjarmasin City has an average of 14.17% which is categorized as less successful. For the calculation of restaurant tax contributions the city of Banjarmasin has an average of 14.04% which means it is still not contributing while from the restaurant tax effectiveness the city of Banjarmasin has an average of 109.13% which can be categorized very effectively.Keywords: Restaurant Tax, Local Revenue.